Sebuah Pemikiran Sosial Profetik Kuntowijoyo dan Paradigma Teologis dalam Islam - Arief Muammar; Marhaban; Miswari Miswari; Ismail Fahmi Arrauf Nasution (Institut Agama Islam Negeri (IAIN) Sultan Amai Gorontalo, 2021)
This article illustrates the stagnation of classical theology and the possibility of constructing prophetic Islamic theology with the social prophetics foundation is built by Kuntowijoyo. The stagnation of classical theology is the main reason for the importance of developing scientific theories, especially social prophetics to answer the problems faced by Muslims. The Kuntowijoyoan Social Prophetics as the conceptual foundation has a humanization, liberation and transcendence orientation. The aiming of this article is to review the philosophical foundations of social prophetics that have a very deep philosophical foundation ranging from philosophy, theology and classical Sufism in Islam as the Indonesian Muslim intellectual ideology today